2003
DOI: 10.1063/1.1581383
|View full text |Cite
|
Sign up to set email alerts
|

45° rotational epitaxy of SrTiO3 thin films on sulfide-buffered Si

Abstract: Sulfide was employed as a buffer layer for the growth of SrTiO3 (STO) thin films on Si. In order to utilize a relationship of a 45° rotational lattice match between Si and STO, ZnS, with almost the same lattice constant as Si, was used as the buffer. The buffer layer showed a partially disordered region at the ZnS/Si interface, owing to steady interdiffusion between ZnS and Si. STO film on ZnS buffered Si showed the rotational epitaxy with respect to Si and sharp STO/ZnS interface. Propagation of stacking faul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
7
0

Year Published

2004
2004
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 10 publications
1
7
0
Order By: Relevance
“…These incidence directions are found corresponding to the (0 0 L) peaks of the perovskite PZNT and STO, so it is evident that the LPE film has a regular epitaxial orientation with (0 0 1) PZNT //(0 0 1) STO . The XRD peak of PZNT {0 0 2} is found to be very close to the STO {0 0 2} peak, which is consistent with the similar lattice constants between them [9,10]. Further investigation on the orientation relationship has been performed by Xray diffraction pole patterns.…”
supporting
confidence: 68%
“…These incidence directions are found corresponding to the (0 0 L) peaks of the perovskite PZNT and STO, so it is evident that the LPE film has a regular epitaxial orientation with (0 0 1) PZNT //(0 0 1) STO . The XRD peak of PZNT {0 0 2} is found to be very close to the STO {0 0 2} peak, which is consistent with the similar lattice constants between them [9,10]. Further investigation on the orientation relationship has been performed by Xray diffraction pole patterns.…”
supporting
confidence: 68%
“…11 Extensive research has been carried out on the growth of STO ͑001͒ on Si ͑001͒ with various single buffer layers and/or multi-buffer layers. 4,[12][13][14][15] Recently, both theoretical and experimental studies have shown that the resulting interfacial structures between silicon and the grown STO thin films depend upon the details of deposition conditions and specific growth sequences. [16][17][18][19] It suggests that differing synthesis routes may lead to epitaxial STO films with different atomic scale structure of the interface.…”
mentioning
confidence: 99%
“…Typical RHEED pattern of ZnS was also clearly seen at all times from the initial growth stage of ZnS (not shown). 13) These observations suggest that the ZnS/Si interface is sharp at the initial growth stage of ZnS but gradually degrades into the disordered phase during the full growth stage of both STO and ZnS, probably arising from the interdiffusion between Si and ZnS. Stacking faults (SFs) because of misfit strain between Si and ZnS lies in {111} planes in Figs.…”
Section: Znsmentioning
confidence: 85%
“…However, STO(100) growth on Si at a wide range of growth temperatures is a difficult task, because growth orientation of STO on Si is very sensitive to the deposition temperature. 9) In this study, ZnS and SrS are used as buffers for the low-and high-temperature growth of STO on Si along the [100] direction, and their structural and interfacial properties are investigated.…”
Section: Introductionmentioning
confidence: 99%